The Empowerment of Teenagers’ Tourism Village - Angga Taufan Dayu; Neneng Islamiah; Nurhasanah Nurhasanah; Yudha Aprizani (Comment: an International Journal of Community Development, 2020)
The success of tourism village development is influenced by many factors. The involvement of the community and all the supporting elements in developing the tourism village becomes the main factor. Community empowerment becomes an alternative solution as an effort to develop tourism village. Batakan village located in Panyipatan District, Tanah laut Regency is a tourist destination that an interesting tourism potential named Batakan. It is surrounded by pine forests around it. The most enabling empowerment for Batakan Village teenagers to support the success of a tourism village development is a tour guide. However, the knowledge and skills that the teenagers have in terms of guidance and English for tour guide is very limited, so it is necessary to conduct guidance and English training for tour guides. The methods used in this training were lecture, discussion, question and answer, drilling, and role play. The results achieved from this activity are 1) the understanding of training participants on the guided tourism improve and 2) English- language training for tour guide, simple English expressions have been mastered